2020
DOI: 10.25182/jgp.2020.15.1.27-36
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Snack for Diabetic Patients from Sago (Metroxylon sp.) Starch and Tempe

Abstract: This study aimed to develop food products made from sago starch (Metroxylon sp.) and tempeh as alternative snacks for diabetics. This study used a completely randomized design (CRD) with two treatment ratios of sago starch to tempeh, F1 (2:1) and F2 (1:1), and two replications for three products, namely puddings, muffins, and cookies. The organoleptic attributes of the products were evaluated by fourty semi-trained panelists. The results of the hedonic test showed that F2 was the formula selected for the puddi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Above that, rice that has been refrigerated and rice with additional coconut oil have fewer calories because the DS is being converted into RS during starch retrogradation (Wang et al 2015). RS contains fewer calories (2 kcal/g) than DS (4 kcal) (Maya et al 2020). This can lower the calories consumed with the same food volume in each food intake.…”
Section: Resultsmentioning
confidence: 99%
“…Above that, rice that has been refrigerated and rice with additional coconut oil have fewer calories because the DS is being converted into RS during starch retrogradation (Wang et al 2015). RS contains fewer calories (2 kcal/g) than DS (4 kcal) (Maya et al 2020). This can lower the calories consumed with the same food volume in each food intake.…”
Section: Resultsmentioning
confidence: 99%
“…Indonesian people usually consume soy in the form of tempeh, tofu, soy sauce, and soy milk which were usually included as side dishes in a meal. A current study conducted in Indonesia found that products made from tempeh are proven to improve blood glucose (Maya et al 2020). Other product such as soy flour based snack bar could be a potential alternative product for healthy or diabetic people.…”
Section: Introductionmentioning
confidence: 95%
“…Sago can also be used as a raw material for other foodstuff such as "bagea", pearl sago, pastries, noodles, biscuits, crackers and laksa (Karim et al 2008;Adrian 2018;Konuma 2018). Sago has a high carbohydrate content, high calories, superior in dietary fiber content (3.69 to 5.96%), and a low glycemic index (GI) value (28), so it is included in the category of functional food (Kusuma et al 2013;Maya et al 2020). Sago also has the potential as a source of nutrition for diabetic patients (Kusuma et al 2013), and is used as other traditional medicine.…”
Section: Introductionmentioning
confidence: 99%